PENGARUH BERKUMUR YOGHURT TERHADAP pH SALIVA PADA SISWA KELAS VIII SMP NEGERI 1 MARTAPURA TIMUR KABUPATEN BANJAR - Puteri, rafilah; Danan, Danan; Nuryati, Sri; Kisworo Utami, Naning (Poltekkes Kemenkes Banjarmasin, 2025)
Yogurt has many benefits for the human body, but due to the lack of information and knowledge about yogurt, it is considered only limited to helping the body's digestive system. Saliva is one of the components that contributes to the acidity level (pH) of the mouth. Saliva as a buffer system to maintain the optimal pH of the mouth, which is pH that tends to be alkaline. If without saliva, then every meal will form an acidic environment that will support the growth of bacteria that damage teeth. This study aims to determine whether there is an effect of yogurt gargling on salivary pH in grade VIII students of SMP Negeri 1 Martapura Timur, Banjar Regency. Research is analytical with a type of pseudo-experimental research with a One Group Pretest-Posttest research design. The study population was 45 people. The sampling technique is Total Sampling with a sample of 45 people. The results of this study showed the average pH of saliva before gargling yogurt was 6.31 and after gargling yogurt was 6.80. Based on the results of statistical tests using the Paired T-Test, ρ (value) = 0.000 < α = 0.05. This study can be concluded that there is an effect of yogurt gargling on salivary pH in grade VIII students of SMP Negeri 1 Martapura Timur, Banjar Regency. It is expected that in order to prefer yogurt as an alternative drink that is better consumed for all circles, yogurt can also further increase the pH of saliva and restore the normal state of saliva.